Numerical study of the passage of natural gas components through C60 fullerite in the low-temperature phase - Borodin, Vladislav I.; Bubenchikov, Alexey M.; Bubenchikov, Mikhail A.; Ovchinnikov, Vyacheslav A.; Chelnokova, Anna Sergeevna (Crystals)
The movement of natural gas components through a crystalline fragment of C-60 fullerite in a simple cubic phase is numerically investigated. The methods of classical molecular physics, the Monte Carlo and Euler approaches, and a step-by-step numerical method of a high order of accuracy are used to study the effects arising from the passage of the particles through the C-60 fullerite. The influence of the characteristics of incoming particles on the permeability of fullerite was analyzed using the results of the performed calculations. The application of the fast integral approach based on the smoothed spherical potential is discussed and compared with the Monte Carlo method.